Condylar Changes and Its Association with Age, TMD, and Dentition Status: A Cross-Sectional Study - Anuna Laila Mathew; Amar A. Sholapurkar; Keerthilatha M. Pai (Hindawi Limited, 2011)
The present study was undertaken to evaluate the prevalence of radiographic changes in the condylar morphology and its association with age, clinical signs and symptoms of temporomandibular dysfunction and dentition status and also to evaluate the intra examiner and inter examiner reliability in assessing condylar changes using panoramic radiographs. A total of 75 subjects were recruited for the study. They were divided into 3 age groups. 20-40 yrs (Group A), 41-60 yrs (Group B) and 61 yrs and above (Group C). In each age group 25 subjects were evaluated both clinically and radiographically. The prevalence of radiographic changes in condylar morphology and symptoms of temporomandibular dysfunction was 81.3% and 18.6%, respectively. Radiographic abnormalities in the mandibular condylar morphology increased with age. They were seen more frequently in patients with clinical signs and symptoms of temporomandibular dysfunction and in patients with loss of teeth. Intra examiner and inter examiner reliability was high indicating a good reliability in assessing the condylar changes using panoramic radiograph.